2007
DOI: 10.1016/j.cardiores.2007.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A novel C-terminal truncation SCN5A mutation from a patient with sick sinus syndrome, conduction disorder and ventricular tachycardia

Abstract: The L1821fs/10 mutation causes the most severe disruption of SCN5A structure for a naturally occurring mutation that still produces current. It has a marked loss-of-function and unique phenotype of SSS, CCD and VT with incomplete penetrance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
3
2

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 30 publications
(54 reference statements)
0
35
3
2
Order By: Relevance
“…Late I Na for both the N406K mutant and WT channels were measured as the leak subtracted inward current remaining at the end of a 700-ms-long depolarization and expressed as a ratio of late/peak I Na as previously reported [18,19]. Representative late I Na traces are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 98%
“…Late I Na for both the N406K mutant and WT channels were measured as the leak subtracted inward current remaining at the end of a 700-ms-long depolarization and expressed as a ratio of late/peak I Na as previously reported [18,19]. Representative late I Na traces are shown in Figure 5.…”
Section: Resultsmentioning
confidence: 98%
“…Альтернативно, эффективность NMD также может обусловливать различную степень выраженности симптомов, которую мы обнаружили у носителей мутации E1823HfsX10. Экспрессия в клетках HEK 293 показала, что, несмотря на серьезное нарушение структуры ка-налов, они генерируют натриевый ток, хотя и резко уменьшенный с преобладанием потери функции (сдвиг кривой активации в сторону бо-лее положительных значений, ускоренная инак-тивация), но также и демонстрируют частичный эффект gain of function (смещение кривой инак-тивации к негативным потенциалам и увеличе-ние плотности позднего натриевого тока INaL) [31]. Эти уникальные функциональные характе-ристики мутации E1823HfsX10 объясняют до-бавление LQTS в сложный фенотип, включаю-щий синдром Бругада, дисфункцию СПУ, нару-шения проводимости и ФП, что влияет на тактику лечения.…”
Section: Discussionunclassified
“…Генотипирование иденти-фицировало мутацию E1823HfsX10 (c.5464_5467delTCTG), искажающую аминокис-лотную последовательность в протяженной об-ласти С-терминального конца α-субъединицы Nav1.5, вслед за местом делеции с образованием нонсенс-кодона, что приводит к преждевремен-ному прекращению синтеза полипептида и об-разованию усеченного и потому нефункцио-нального белка. Для этого варианта показана связь с синдромом Бругада, остановкой сердца, СССУ, нарушениями сердечной проводимости и LQTS [30,31]. Последующий скрининг семьи показал накопление случаев ВСС и СВДС (дво-юродный брат -10 мес, брат -25 лет), Бругада-паттерн I типа, АВ-блокаду I степени и ФП у дя-ди (57 лет), ФП и синусовую брадикардию без признаков изменений реполяризации у отца (66 лет) (рис.…”
Section: результатыunclassified
“…See observed in combined mutant channel indicated that both fast inactivation and slow inactivation were impaired. Decelerated decay of macroscopic currents, stemming from delayed onset of inactivation, often occurs in combination with a persistent current (25). A slower current decay alone should not directly lengthen APD, but might affect voltage-dependent activity of other outward or inward currents that are crucial for APD, since additional sodium inward current was generated during the early phase of the action potential plateau, which resulted in augmentation of the net ionic current (24).…”
Section: Discussionmentioning
confidence: 99%